Post-anesthetic CPS and EQUUS-FAP scores in surgical and non-surgical equine patients: an observational study - Reed, Rachel Anne; Krikorian, Anna M.; Reynolds, Rose M.; Holmes, Brittany T.; Branning, Megan M.; Lemons, Margaret B.; Barletta, Michele; Quandt, Jane E.; Burns, Charlotte C.; Dantino, Stephanie C.; Sakai, Daniel M. (Frontiers in Pain Research, 2023)
Background: Equine pain scoring may be affected by the residual effect of anesthetic drugs. Objectives: To compare pain scores in the hours immediately following anesthetic recovery to baseline pre-anesthetic scores in equine patients undergoing surgical and non-surgical procedures. Study Design: Clinical observational study Methods: Fifty adult horses undergoing anesthesia for surgical or non-surgical procedures were enrolled. Horses underwent pain scoring using the Composite Pain Score (CPS) and Equine Utrecht University Scale for Facial Assessment of Pain (EQUUS-FAP) prior to anesthesia (T0) and following anesthetic recovery to standing, every hour for 5 hours (T1-T5). Data were analyzed using generalized linear mixed effects model. A post-hoc Dunnett’s test for multiple comparisons was performed for variables where an effect was detected. Results: Mean (95% confidence interval) CPS scores for T0-T5 were 1.6 (1.2-2.0), 6.8 (6.0-7.6), 5.1 (4.3-5.9), 4.3 (3.4-5.2), 3.7 (2.8-4.6), and 2.8 (2.0-3.6) and EQUUS-FAP scores were 0.6 (0.3-0.9), 3.0 (2.5-3.5), 1.9 (1.6-2.2), 1.1 (0.8-1.4), 0.6 (0.4-0.8), and 0.7 (0.4-1.0), respectively. For the CPS, scores greater than 5, and for the EQUUS-FAP scores greater than 3, are consistent with minor pain. There was no effect of type of procedure (surgical vs non-surgical) on CPS or EQUUS-FAP scores. There was an effect of time with CPS scores significantly greater than baseline at T1-T5 and EQUUS-FAP scores significantly greater than baseline at T1 and T2. Main Limitations: Discomfort caused by hoisting was not quantified and it was difficult to ascertain if this affected the results. Conclusions: Post-anesthetic pain scores may be influenced by the residual effect of anesthetic agents for as long as 5 hours and 2 hours for the CPS and EQUUS-FAP, respectively.